Determination of Lewis and Brönsted acid sites by gas flow-injection technique - Musthofa, Malik; Karim, Ainul Hakimah; Ahmad Fadzlillaah, Nurrulhidayah; Annuar, Nur Hazirah Rozali; Jalil, Aishah Abdul; Triwahyono, Sugeng (UTM Press, 2010)
Gas flow-injection technique pyridine-FTIR was studied for determination of Lewis and Brönsted acid sites on the solid super acid catalysts. The system consists of stainless steel gas cell which can be heated up to 623 K, CaF2 windows, pyridine injection port and double liquid nitrogen trap for removal of moisture. Pure nitrogen gas and pyridine were used as a carrier and probe molecule. Pyridine was injected to the sysem at 423 K followed by flushing of N2 gas through double liquid nitrogen trap at 423 for 1 h and at 573 K for 30 min. All spectra were recorded at room temperature. This technique gave similar results to those of taken by vacuum system for HZSM-5, Pt/SO4 2--ZrO2, Al2O3 catalysts.